New insights into plant natriuretic peptide evolution: From the lysogenic conversion in Xanthomonas to the lateral transfer to the whitefly Bemisia tabaci - Patané, José S.L.; Moreira, Leandro M.; de Melo Teixeira, Marcus; Martins Jr, Joaquim; Setubal, João C.; Varani, Alessandro M. [UNESP] (Elsevier, 2022)
Plant natriuretic peptide-like (PNP) are signaling molecules related to adaptive responses to stress. The Arabidopsis thaliana PNP (AtPNP-A) is capable of modulating catalase 2 (CAT2) and rubisco activase (RCA) activity in some circumstances. Interestingly, many plant-pathogens co-opted PNP-like molecules to their benefit. For instance, the citrus pathogen Xanthomonas citri carries a PNP-like (XacPNP) that can mimic and regulate plant homeostasis, and many phytopathogenic fungi carry effectors (e.g., Ave1 and AvrLm6) that are indeed PNP-like homologs. This work investigates the PNP-like evolution across the tree of life, revealing many parallel gains and duplications in plant and fungi kingdoms. All PNP-like proteins in the final dataset are structurally similar, containing the AtPNP-A active domains modulating CAT2 activity and RCA interaction. Comparative genomics evinced that XacPNP is a lysogenic conversion factor associated with a Myoviridae-like prophage identified in many Xanthomonas species. Surprisingly, a PNP-like homolog was identified in Bemisia tabaci, an important agricultural pest, being to date the second example of lateral gene transfer (LGT) from plant to the whitefly. Moreover, the Bemisia PNP-like homolog can also be considered a potential new effector of this phloem-feeding insect. Noteworthy, the whiteflies infest many plants carrying PNP-like copies and interact with some of their bacterial and fungal pathogens, strongly suggesting complex recipient/donor traits of PNP by LGT and bringing new insights into the evolution of host-pathogen arms race across the tree of life.
Keywords: Effectors; Genome evolution; Lateral gene transfer; Plant-insect interactions; Plant-pathogen interactions; Transduction